2016
DOI: 10.1039/c6ra16328a
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature gas–solid carbonation of magnesia and magnesium hydroxide promoted by non-immersive contact with water

Abstract: From high-pressure gas–solid thermogravimetry, the presence of water at high relative humidity (>25% RH) caused a drastic acceleration in the rate of CO2 absorption into MgO and Mg(OH)2 producing magnesite and hydrocarbonate precursors below 200 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…However, its formation in low temperature environments is unlikely to occur on short timescales (Hänchen et al, 2008;Saldi et al, 2012), thus making the hydrated Mg-carbonates the targets for CO2 storage at near Earth's surface temperatures. Although hydromagnesite, dypingite and nesquehonite are common products of ultramafic rock weathering (Assima et al, 2014;Bea et al, 2012;Boschi et al, 2009;Chaka et al, 2016;Felmy et al, 2012;Garcia del Real et al, 2016;Gras et al, 2017;Highfield et al, 2016;Hövelmann et al, 2012;Kristova et al, 2014;Loring et al, 2012;Montes-Hernandez et al, 2012;Pronost et al, 2011;Schaef et al, 2011;Zhao et al, 2010), previous studies on their formation that used Mg isotope systematics suggested a continuous exchange of Mg isotopes between the solid and the fluid phase at ~25 o C (e.g., Mavromatis et al, 2012;Shirokova et al, 2013). Similar observations were made based on the δ 13 C value of the solid and the dissolved inorganic carbon composition of the forming fluid (Mavromatis et al, 2015) and likely reflect the high reactivity of these…”
Section: Implications For Co2 Storage In Hydrous Mg-carbonatesmentioning
confidence: 99%
“…However, its formation in low temperature environments is unlikely to occur on short timescales (Hänchen et al, 2008;Saldi et al, 2012), thus making the hydrated Mg-carbonates the targets for CO2 storage at near Earth's surface temperatures. Although hydromagnesite, dypingite and nesquehonite are common products of ultramafic rock weathering (Assima et al, 2014;Bea et al, 2012;Boschi et al, 2009;Chaka et al, 2016;Felmy et al, 2012;Garcia del Real et al, 2016;Gras et al, 2017;Highfield et al, 2016;Hövelmann et al, 2012;Kristova et al, 2014;Loring et al, 2012;Montes-Hernandez et al, 2012;Pronost et al, 2011;Schaef et al, 2011;Zhao et al, 2010), previous studies on their formation that used Mg isotope systematics suggested a continuous exchange of Mg isotopes between the solid and the fluid phase at ~25 o C (e.g., Mavromatis et al, 2012;Shirokova et al, 2013). Similar observations were made based on the δ 13 C value of the solid and the dissolved inorganic carbon composition of the forming fluid (Mavromatis et al, 2015) and likely reflect the high reactivity of these…”
Section: Implications For Co2 Storage In Hydrous Mg-carbonatesmentioning
confidence: 99%
“…The multitude of potential metastable hydrated 69 phases complicates prediction of Mg-carbonate formation and thus the stability of the CO 2storing phase (Königsberger et al, 1999;Hopkinson et al, 2008Hopkinson et al, , 2012Hänchen et al, 2008;Montes-Hernandez et al, 2012;Kristova et al, 2014). To reduce some of the ambiguity in the prediction of Mg-carbonate mineral formation under various conditions, in this study we determine the solubility of nesquehonite [MgCO 3 •3H 2 O] and dypingite [Mg 5 (CO 3 ) 4 (OH) 2 •(5 or)8H 2 O], two commonly observed products of carbon mineralization in ultramafic materials (Wilson et al, 2006(Wilson et al, , 2011(Wilson et al, , 2014Boschi et al, 2009;Zhao et al, 2010;Pronost et al, 2011;Schaef et al, 2011;Bea et al, 2012;Loring et al, 2012;Montes-Hernandez et al, 2012;Assima et al, 2012Assima et al, , 2014cHövelmann et al, 2012;Felmy et al, 2012;Beinlich and Austrheim, 2012;Schaef et al, 2013;Harrison et al, 2013aHarrison et al, , 2015Harrison et al, , 2016Harrison et al, , 2017Power et al, 2013aPower et al, , b, c, 2014bKristova et al, 2014;McCutcheon et al, 2016;Chaka et al, 2016;Garcia del Real et al, 2016;Highfield et al, 2016;Gras et al, 2017;McCutcheon et al, 2017), and the transformation process that converts nesquehonite to dypingite. Both nesquehonite and dypingite are readily formed during reaction of Mg-rich minerals with CO 2 at ambient te...…”
Section: Introduction 26 27mentioning
confidence: 99%
“…(31) Consistent with previous studies carrying out carbonation of Mg precursors at low pressure and temperature, (19,31,47) none of the diffraction patterns in Figures 4c and 4d contain peaks associated with magnesite, which is only known to form at higher temperature and pressure. (48,49) Clear evidence of carbonate formation was also observed in SEM images of both types of samples (Figures 4e and 4f). For the cured standard samples, rosette-like features are seen that are characteristic of hydromagnesite, as observed in other reactive Mg-based systems.…”
Section: Carbonation Curing Of Mg(oh) 2 Mixturesmentioning
confidence: 60%
“…For example, differences in the density and size of agglomerated particles in the source material can be expected to alter the local concentrations of CO2 and H2O within the agglomerates, with higher densities and larger agglomerate sizes resulting in lower concentrations of reactant species within the interior of the agglomerates. (54) Since reaction rate expressions for different reaction pathways can have different reaction orders with respect to reactants, (48,49) it stands to reason that relative changes in local concentrations of H2O and CO2 within a specimen can lead to different products. However, other possible explanations, including interactions with impurity calcite crystallites and/or the formation of CO2-rich bubbles within nanoscopic voids within the particles,(54) cannot be ruled out at this time.…”
Section: Carbonation Curing Of Mg(oh) 2 Mixturesmentioning
confidence: 99%